Eimerias de los bovinos de Costa Rica II. Incidencia en terneros - Ruiz, Armando (1961)
The fecal matter of one hundred calves of four different regions of the country was examined for the presence of Eimeria oocysts. Forty nine of the calves were found lo be parasitized, among which eleven presented a mixed infection. The species found and their incidence is as follows: E. bovis, 31 percent; E. alabamensis, 20 per cent; E. ellipsoidalis, 4 per cent; E. subsphaerica, 3 per cent; E. zurni, 2 per cent and E. auburnensis, 1 per cent. E. alabamensis, E. subsphaerica and E. auburnensis are recorded for the first time in Costa Rica.